FAKTOR – FAKTOR MEMPENGARUHI KOMITMEN ORGANISASI PEGAWAI BANK SUMSEL BABEL CABANG MUARADUA - Mardalena, Ervin; ., Noviansyah (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2025)
This study aims to determine the influence of personality and interpersonal communication on organizational commitment of employees of Bank Sumsel Babel Muaradua Branch. The data analysis technique used was Multiple Linear Regression. Based on the results of the partial analysis, there was a significant influence of personality on the organizational commitment of the employees of Bank Sumsel Babel Muaradua Branch with a t value of 4.757. Variables and interpersonal communication had no significant influence on organizational commitment of employees of Bank Sumsel Babel Muaradua Branch with a t value of 0.725. Simultaneously, it was found that there was an influence of personality and interpersonal communication on the organizational commitment of the employees of Bank Sumsel Babel Muaradua Branch. The coefficient of determination (R2) obtained was 0.518. This showed that the contribution of personality and interpersonal communication influenced on organizational commitment was 51.8% while the remaining 48.2% was influenced by other variables not mentioned in this study such as leadership style, trust in leaders, organizational culture.